The relationship between Islamic religiosity, depression and anxiety among Muslim cancer patients. - Nadzirah Ahmad Basri; Gan, Chun Hong; Ng, Alvin Lai Oon * (2014)
There is a growing body of evidence that religiosity and spirituality can buffer depression and anxiety and support the healing process in cancer patients. However, literature on the role of Islamic religiosity in the healing of Muslim cancer patients are few. This study aimed to examine the relationship between Islamic religiosity with depression and anxiety in Muslim cancer patients. 59 cancer patients were approached in oncology day care and ward at a Malaysian government hospital and in a cancer support group activity. Patients completed the Muslim Religiosity and Personality Inventory which assessed their Islamic religiosity scores through the constructs of Islamic beliefs and Manifestation of Islamic belief. Self-rated depression and anxiety were assessed using validated Beck Depression Inventory and Beck Anxiety Inventory in Malay. Ten of the patients were interviewed about their spiritual experiences and emotions. Questionnaire findings revealed a significant negative correlation between Islamic religiosity with depression and anxiety. Higher manifestation of Islamic belief was associated with lower depression while higher Islamic belief was associated with higher education. Higher Islamic religiosity was associated with older age, married and pensioned patients. Interview findings revealed that being ill brought the patients closer to God and many thanked God for the blessing and time spared for them to repent and do more good actions. All of them used prayers to heal their pain. Patients also reported strong feelings of anger, frustration and sadness after the initial diagnosis which slowly disappeared as they began to accept their illness as a blessing in disguise. It is concluded that there is a need to respond to the meaning and values given to human existence besides responding to physical and mental suffering in cancer patients.